Religions in Shakespeare's Writings - Urban, David V. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Offering a wide range of scholarly perspectives, Religions in Shakespeare's Writings explores Shakespeare's depictions, throughout his canon, of various religions and matters related to them. This collection's fifteen essays explore matters pertaining to Catholic, Anglican, and Puritan Christianity, the Albigensian heresy of the high middle ages, Islam, Judaism, Roman religion, different manifestations of religious paganism, and even the "religion of Shakespeare" practiced by Shakespeare's nineteenth-century admirers. These essays analyze how Shakespeare depicts both tensions between religions and the syntheses of different religious expressions on topics as diverse as Shakespeare's varied portrayals of the afterlife, religious experience in Measure for Measure, and Black natural law and The Tempest. This collection also explores the political ramifications of religion within Shakespeare's works, as well as Shakespeare's multifaceted uses of the Bible. Additionally, while this collection does not present a Shakespeare whose particular religious beliefs can definitely be known or are displayed uniformly throughout his canon, various essays consider to what extent Shakespeare's individual works demonstrate a Christian foundation. Contributors include John D. Cox, Cyndia Susan Clegg, Grace Tiffany, Matthew J. Smith, Bethany C. Besteman, Sarah Skwire, Feisal Mohamed, Benedict J. Whalen, Benjamin Lockerd, Bryan Adams Hampton, Debra Johanyak, John E. Curran, Emily E. Stelzer, David V. Urban, and Julia Reinhard Lupton.